Speaking Content Analysis in Indonesian Vocational High School English Textbook - Uswatun Khasanah; Ro'ifah Ro'ifah; Sulton Dedi Wijaya (International Journal of Language Teaching and Education, 2022)
This study aimed to determine the appropriateness of speaking content in Class XII vocational high school English textbooks in light of the new Indonesian curriculum, the Kurikulum Merdeka. The transition from the Kurikulum 2013 to the Kurikulum Merdeka requires teachers to modify teaching materials, making it important to understand if existing English textbooks can be adapted. The research methodology was qualitative and descriptive, utilizing document analysis of the students' English textbook, "Bahasa Inggris". Data was collected through document checklists and interviews, with a focus on speaking assignments. The study was guided by Nunan and Brown's theory and the results indicated that the speaking tasks in the textbook met five criteria for effective speaking assignments, as specified by Brown's theory. The majority of the speaking assignments were intensive speaking with good to excellent rankings, followed by imitative, responsive, interactive, and extensive speaking. The results suggest that the textbook's speaking content is suitable for use in teaching materials aimed at achieving the speaking skills outlined in the Kurikulum Merdeka.